GENETIC EVALUATION OF LAYING TRAITS IN IRANIAN INDIGENOUS HENS USING UNIVARIATE AND BIVARIATE ANIMAL MODELS - A. Jafarnejad; M.A. Kamali; S.J. Fatemi; M. Aminafshar (Journal of Animal and Plant Sciences, 2017)
The present study was carried out with the aim of estimating genetic parameters as well as evaluating genetic improvement in Iranian native chickens to assess the effectiveness of selection programs performed in Azerbaijan native fowl breeding station. The data on pedigree and performance was collected through five consecutive generations consisted of 4400 hens and roosters. Considered traits were body weight at week 12 (BW12), total number of eggs laid during the first 12 weeks after flock maturity (EN), mean egg weight at 28, 30 and 32 weeks (MEW) and age at sexual maturity (ASM). The (co) variance components, heritabilities, correlations between traits as well as breeding values were estimated through univariate and bivariate animal models using WOMBAT software. Heritability estimates for BW12, EN, MEW and ASM, using four different univariate animal models, were 0.25±0.08, 0.18±0.05, 0.24±0.03 and 0.43±0.07, respectively. A bivariate animal model was applied to estimate genetic correlations between traits. Geneticcorrelations were in a range from-‌0.10 to -‌0.63. The highest and lowest genetic correlation were betweenASM and MEW (0.30± 0.06) and ASM and EN (-0.63± 0.02), respectively. Regression coefficient of average breeding values on generation number were positive and significant for BW12 and EN, indicating positive trend that confirmed genetic progress in these traits. However, MEW as well as ASM responded negatively to genetic improvement.
Keywords: Heritability; Genetic correlation; Genetic trend; laying traits; Animal model